An Overview on Mitochondrial-Based Therapies in Sepsis-Related Myocardial Dysfunction: Mitochondrial Transplantation as a Promising Approach. (6th June 2022) - Mokhtari, Behnaz; Yavari, Rana; Badalzadeh, Reza; Mahmoodpoor, Ata
Abstract : Sepsis is defined as a life-threatening organ failure due to dysregulated host response to infection. Despite current advances in our knowledge about sepsis, it is still considered as a major global health challenge. Myocardial dysfunction is a well-defined manifestation of sepsis which is related to worse outcomes in septic patients. Given that the heart is a mitochondria-rich organ and the normal function of mitochondria is essential for successful modulation of septic response, the contribution of mitochondrial damage in sepsis-related myocardial dysfunction has attracted the attention of many scientists. It is widely accepted that mitochondrial damage is involved in sepsis-related myocardial dysfunction; however, effective and potential treatment modalities in clinical setting are still lacking. Mitochondrial-based therapies are potential approaches in sepsis treatment. Although various therapeutic strategies have been used for mitochondrial function improvement, their effects are limited when mitochondria undergo irreversible alterations under septic challenge. Therefore, application of more effective approaches such as mitochondrial transplantation has been suggested. This review highlights the crucial role of mitochondrial damage in sepsis-related myocardial dysfunction, then provides an overview on mitochondrial-based therapies and current approaches to mitochondrial transplantation as a novel strategy, and proposes future directions for more researches in this field.